Il dibattito sul diaconato femminile ai tempi di papa Francesco - Piola, Alberto (La scuola cattolica, 2025)
The article, having recalled the beginnings of the debate on women’s diaconate during the post-conciliar period, aims to discuss how this debate has been developed during Pope Francis’ Pontificate, especially by those who retain possible and urgent the admission of women to the first grade of the sacrament of Holy Orders. It is a debate which has not yet reached a conclusion: there is a lack of consensus, and it would appear there are still tensions in the Church which at this moment would indicate against the taking of adecision. The article ends by proposing the case of women’s diaconate as a significant example of the presence of tensions in the living out of ecclesial synodality.